Green Synthesis Of Silver Nanoparticles And Evaluation Of Their Antibacterial Activity Against Selected Pathogens - KM, Dufaida; V, Razifa; K, Femina (Journal of Neonatal Surgery, 2025)
Green synthesis of silver nanoparticles (AgNPs) using plant extracts has emerged as an eco-friendly alternative to traditional methods , offering benefits like safety, sustainability, and enhanced bioactivity . This study focuses on the synthesis of AgNPs using leaf extracts from Adathoda vasica, Plectranthus amboinicus, Pimenta dioica and evaluates their antibacterial properties against selected pathogens. The plant-mediated synthesis relies on phytochemicals—such as flavonoids, terpenoids, and phenolic compounds—which act as both reducing and stabilizing agents, facilitating the conversion of silver ions (Ag⁺) to elemental silver (Ag⁰) and providing stability to the nanoparticles. The formation of AgNPs confirmed by a characteristic color change and spectrophotometric analysis, showing absorption peaks between 350–500 nm, indicative of surface plasmon resonance. The synthesized nanoparticles were purified and tested for antibacterial efficacy using the agar well diffusion method against pathogens, including Escherichia coli, Salmonella spp., Pseudomonas spp., and Staphylococcus spp. Results showed that AgNPs exhibit broad-spectrum antibacterial activity, especially AgNPs synthesized from Adathoda vasica. These findings reveal the potential of green-synthesized AgNPs in medical and environmental applications as an alternative to conventional antibiotics, especially in combating multidrug-resistant bacteria.